2015
DOI: 10.1186/1471-2253-15-16
|View full text |Cite
|
Sign up to set email alerts
|

Temperature modulation with an esophageal heat transfer device- a pediatric swine model study

Abstract: Background: An increasing number of conditions appear to benefit from control and modulation of temperature, but available techniques to control temperature often have limitations, particularly in smaller patients with high surface to mass ratios. We aimed to evaluate a new method of temperature modulation with an esophageal heat transfer device in a pediatric swine model, hypothesizing that clinically significant modulation in temperature (both increases and decreases of more than 1°C) would be possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…5,26 Relatively newer methods of intraoperative thermal regulation include intravascular, esophageal, and skin surface modalities. 5,16,17,[27][28][29][30] As cool IV fluids have been identified as a risk factor for the development of intraoperative hypothermia, the use of IV warming catheters has been shown to confer the ability to decrease ambient temperatures to 23.9-29.4°C with conservation of patient normothermia among patients with ≥25% TBSA burns. 5,16,17,20,21 Although there is a lack of literature which demonstrates its efficacy in burn patients specifically, esophageal heat exchange systems have been shown to be efficacious in supplementing or replacing surface warming where the latter is not possible, producing a mean warming of .5°C per hour among patients undergoing non-burn surgeries and .29°C per hour in porcine models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,26 Relatively newer methods of intraoperative thermal regulation include intravascular, esophageal, and skin surface modalities. 5,16,17,[27][28][29][30] As cool IV fluids have been identified as a risk factor for the development of intraoperative hypothermia, the use of IV warming catheters has been shown to confer the ability to decrease ambient temperatures to 23.9-29.4°C with conservation of patient normothermia among patients with ≥25% TBSA burns. 5,16,17,20,21 Although there is a lack of literature which demonstrates its efficacy in burn patients specifically, esophageal heat exchange systems have been shown to be efficacious in supplementing or replacing surface warming where the latter is not possible, producing a mean warming of .5°C per hour among patients undergoing non-burn surgeries and .29°C per hour in porcine models.…”
Section: Discussionmentioning
confidence: 99%
“…5,16,17,20,21 Although there is a lack of literature which demonstrates its efficacy in burn patients specifically, esophageal heat exchange systems have been shown to be efficacious in supplementing or replacing surface warming where the latter is not possible, producing a mean warming of .5°C per hour among patients undergoing non-burn surgeries and .29°C per hour in porcine models. 27,28 Additionally, a variety of skin surface modalities, using heated air, water, or gel are commonly employed to reduce perioperative hypothermia. 29 However, these methods have limited applicability among severely burned patients in the acute setting due to their interference with the surgical fields in trauma bays, BICU, and ORs.…”
Section: Discussionmentioning
confidence: 99%
“…The Department of Emergency Medicine evaluated the ECD on two key criteria: 1) that the clinical performance of the ECD was equivalent to the surface system in use, and 2) that staff members experienced less interference with clinical tasks. Results from published pre-clinical data [11][12][13][14], case studies [15][16][17][18], and prospective clinical evaluations [19] suggested that equivalent performance was attainable. The internal placement of the device, which replaces a standard OG tube (Figure 1), also suggested that reduced interference with clinical tasks was likely.…”
Section: Evaluating a New Ttm Devicementioning
confidence: 99%